Pembentukan Karakter Disiplin dalam Institusi Pendidikan Islam: Studi Kasus di MI Roudlotul Huda Kota Semarang - Dina Damayanti; Ali Imron; Hamid Sakti Wibowo (Bulletin of Indonesian Islamic Studies, 2022)
Discipline character building in students is needed and must be instilled early in the learning process. This paper aims to analyze the teacher's efforts in shaping the disciplined character of students at MI Roudlotul Huda Sekaran, Gunung Pati, Semarang. This paper uses a qualitative field research type. Data were collected by observation, interviews, and documentation. Checking the validity of the data is done by using the triangulation technique. The data analysis method used is in the form of data reduction, data presentation, and concluding. The results showed that the teacher's efforts in shaping the disciplined character of MI Roudlotul Huda Sekaran Gunung Pati Semarang students included the synergy of the headmaster and the teachers in setting good examples, habituation of positive activities, and exemplary discipline. The supporting factors for the formation of student character are good cooperation from school personnel, good communication between parents, teachers, students, the community, a positive school environment, and teachers who are enthusiastic about acting as models or leaders. While the factors that hinder student discipline are readiness in students, environmental factors, and family factors